The Linked Employer–Employee Study of the Socio-Economic Panel (SOEP-LEE): Content, Design and Research Potential - Michael Weinhardt; Alexia Meyermann; Stefan Liebig; Jur̈gen Schupp (Jahrbücher für Nationalökonomie und Statistik, 2017)
The data set presented in this article results from a project to produce a Linked-Employer-Employee data set for the Socio-Economic Panel (SOEP). 1 In 2012/13, a survey of German employers was conducted using face-to-face and paper-and-pencil interviews (N0.167em=0.167em1,708; response rate0.167em=0.167em30.10.166em%). Establishments were sampled based on address information provided by employed participants from the SOEP. The SOEP is a longitudinal study of German households that are representative of the German population, repeatedly surveying about 20,000 individuals and 10,000 households each year. 2 The information obtained from both surveys can be linked in order to create a linked employer–employee data set concerning organizational context and individual outcomes (N0.167em=0.167em1,834, mostly one employee per employer). The information collected in the LEE study reported enrich and enhance the existing individual-level and household-level SOEP data with supplemental data about the workplace and the employees' working conditions. In contrast to the SOEP core study, the SOEP-LEE data set contains more detailed and independent information concerning the work context. This way, the LEE data can be used to investigate the organizational impact on the genesis of social inequalities and the individual development of the life course. The SOEP-LEE study specifically sought to obtain information about inter-organizational as well as intra-organizational heterogeneities such as forms of employment (part-time, full-time), temporary work, and similar atypical forms of employment, as well as about other factors, such as gender composition, the age of the employees, and the wage structure of the establishment. The overall aim was to investigate social inequalities and their relation to employers and organizations (e.0.167emg., to determine how organizational structures and practices influence social inequality at the individual level). A detailed project report of the study can be found in Weinhardt et0.167emal. (2016).
Keywords: 330